"Un-hiding" knowledge in organizations: the role of climate for innovation, social exchange and social identification. Issue 1 (21st February 2020) - Sukumaran, Rahul; Lanke, Parijat
Abstract : Purpose: Knowledge hiding is a phenomenon in organizations that is commonly observed to be detrimental to the performance of employees. The purpose of this paper is to propose a conceptual framework, which uses social exchange theory and social identity theory to advance an understanding of how climate for innovation can dampen the negative impact of knowledge hiding on performance. Design/methodology/approach: We have reviewed papers on the concept of knowledge hiding, social identity theory, social exchange theory as well as the literature on climate for innovation, in order to draw the relationships and propose a framework. Findings: Based on the papers reviewed, this study conceptually advances the understanding that an organizational factor such as "climate for innovation" would prove beneficial to check and reduce knowledge hiding behavior i.e. unhide the knowledge and subsequently improve performance of employees in organizations. Practical implications: This study proposes climate for innovation, as a factor that would influence the negative impact of knowledge hiding on performance. It is under the control of the managers to create such environment in their teams and the work settings, which would help un-hide the knowledge, and thereby promoting performance at workplace. Originality/value: This paper contributes to the literature on knowledge hiding as well as the climate for innovation. This is the first work to propose an interaction of climate of innovation with knowledge hiding behavior and their overall impact on performance. The framework is explained in a simple term, to bridge the gap between academics and practitioner world.